High-entropy spinel oxide loaded graphene catalyst, preparation method thereof and flexible zinc air battery

By loading graphene catalysts with high entropy spinel oxides, the problem of slow catalytic kinetics of flexible zinc-air batteries in low-temperature environments was solved, efficient ORR/OER catalysis was achieved, the discharge power and low-temperature adaptability of the battery were improved, and it has the advantages of low cost and environmental protection.

CN120690873APending Publication Date: 2025-09-23SANYA MARINE OIL & GAS RESEARCH INSTITUTE NORTHEAST PETROLEUM UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510826074.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-19
Publication Date
2025-09-23

AI Technical Summary

Technical Problem

Existing flexible zinc-air batteries have slow catalytic kinetics in low-temperature environments, and the solubility and diffusion rate of oxygen are reduced, resulting in a decrease in the electrocatalytic reaction rate, an increase in overpotential, an intensification of the polarization effect, and a decrease in energy conversion efficiency. Commercial catalysts are expensive and have poor low-temperature stability.

Method used

High-entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles loaded with reduced graphene oxide (rGO) catalyst were prepared by hydrothermal method and used as cathode catalyst for flexible zinc-air batteries to improve ORR/OER catalytic activity and stability.

Benefits of technology

It significantly improves the discharge power and low-temperature adaptability of flexible zinc-air batteries in low-temperature environments, replaces commercial precious metal catalysts, demonstrates excellent catalytic activity and stability, is low-cost, green and environmentally friendly, and can be mass-produced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a high-entropy spinel oxide loaded graphene catalyst, a preparation method thereof and a flexible zinc air battery, and belongs to the technical field of electrocatalysis. The high-entropy spinel oxide loaded graphene catalyst is a (FeCrCuNiMn) 3O4 / rGO composite material, the (FeCrCuNiMn) 3O4 is a high-entropy oxide with a spinel type structure, and the rGO is reduced graphene oxide. The catalyst shows excellent catalytic performance in oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), and has relatively high electrochemical activity, stability and conductivity. In a low-temperature environment, the flexible zinc-air battery driven by the catalyst can significantly reduce battery polarization in charging and discharging processes, the power density of the flexible zinc-air battery is improved, and the overall performance and low-temperature adaptability of the battery are effectively improved. And the requirements of high efficiency and low-temperature adaptability of the flexible zinc-air battery at low temperature are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalysis, and in particular relates to a high-entropy spinel oxide-loaded graphene catalyst, a preparation method thereof, and a flexible zinc-air battery. Technical Background

[0002] With the increasing global energy demand and increasingly severe environmental problems, the development of efficient and sustainable energy storage batteries has become a key issue in today's scientific research.

[0003] Against the backdrop of increasingly challenging energy challenges, zinc-air batteries (Zn-air batteries) have become a key development direction in energy storage technology due to their high energy density, low cost, and environmentally friendly advantages. However, low temperatures significantly impact the performance of flexible Zn-air batteries, restricting their practical application under these conditions. At low temperatures, flexible Zn-air batteries face sluggish catalytic kinetics, particularly during the redox reaction (ORR) and oxygen evolution reaction (OER). Low temperatures significantly reduce the solubility and diffusion rate of oxygen, thereby slowing the electrocatalytic reaction rate and limiting the reaction kinetics. This leads to increased overpotential, exacerbated polarization effects, and reduced energy conversion efficiency in flexible Zn-air batteries. Exploring efficient bifunctional ORR / OER electrocatalysts for flexible Zn-air batteries operating at low temperatures is a major challenge. Currently, commercial Zn-air battery cathode catalyst combinations are Pt / C + RuO2 and Pt / C + IrO2. These noble metal commercial catalysts are high cost, scarce, and have poor low-temperature stability, limiting their application in low-temperature flexible Zn-air batteries. Therefore, developing bifunctional ORR / OER electrocatalysts that can efficiently drive flexible Zn-air batteries at low temperatures is highly urgent. Spinel oxides are expected to be effective electrocatalysts. High-entropy spinel oxides (HESO) are composed of five or more metal cations and have a single-phase structure. They exhibit high entropy effects, lattice distortion effects, and cocktail effects. HESO is a strong candidate for electrocatalysts. However, there are no reports on HESO materials that can achieve efficient bifunctional ORR / OER electrocatalysts in flexible zinc-air batteries under low-temperature environments. Summary of the Invention

[0004] In response to the shortcomings of the prior art, the present invention provides a high-entropy spinel oxide-loaded graphene catalyst, a preparation method thereof, and a flexible zinc-air battery. The high-entropy spinel oxide-loaded graphene catalyst has excellent bifunctional ORR / OER catalytic activity and stability. Under low-temperature conditions, the high-entropy spinel oxide-loaded graphene catalyst is used as a cathode bifunctional electrocatalyst to drive a low-temperature flexible zinc-air battery. Compared with the commercial electrocatalyst Pt / C+RuO2, the discharge power and low-temperature adaptability of the flexible zinc-air battery driven by it can be effectively improved. The preparation method of the high-entropy spinel oxide-loaded graphene catalyst of the present invention is simple and effective, low-cost, the synthesis method is controllable, green and environmentally friendly, and can be mass-produced. It has practical application prospects in the field of flexible zinc-air batteries under low-temperature conditions.

[0005] The first technical problem to be solved by the present invention is: a high entropy spinel oxide supported graphene catalyst.

[0006] The second technical problem to be solved by the present invention is: a method for preparing a high-entropy spinel oxide-supported graphene catalyst.

[0007] The third technical problem solved by the present invention is: a flexible zinc-air battery driven by the high-entropy spinel oxide-loaded graphene catalyst of the present invention, specifically a flexible zinc-air battery at room temperature and low temperature environments, especially a flexible zinc-air battery at low temperature environments.

[0008] In order to solve the above-mentioned first technical problem, the technical solution adopted by the present invention is:

[0009] The invention discloses a high-entropy spinel oxide-supported graphene catalyst, whose molecular formula is: (FeCrCuNiMn)3O4 / rGO; wherein high-entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles are uniformly dispersed on the surface of reduced graphene oxide (rGO) sheets.

[0010] In terms of mass ratio, high entropy spinel oxide (FeCrCuNiMn) 3 O 4 nanoparticles: reduced graphene oxide (rGO) = 1: (1.1-1.5), preferably 1:1.2.

[0011] High entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles are high entropy oxides with a spinel structure.

[0012] In the (FeCrCuNiMn)3O4 / rGO, the mass percentages of Fe, Cr, Cu, Ni, and Mn are between 5% and 20%, and the mass percentages of the individual elements differ by no more than 8%, preferably Fe: 14.1-14.2%, Cr: 9.1-9.2%, Cu: 16.1-16.2%, Ni: 16.5-16.7%, and Mn: 14.2-14.3%, and the ratio of the sum of the molar numbers of the five elements to the molar number of O is 3:4.

[0013] The high-entropy spinel oxide-supported graphene catalyst has catalytic performance in the ORR and / or OER process. Electrochemical tests show that in alkaline KOH solution, the ORR half-wave potential can reach 0.80V to 0.85V, and the OER overpotential can reach 350mV to 360mV.

[0014] Specifically:

[0015] For the ORR process, the ORR catalytic performance of the high entropy spinel oxide supported graphene catalyst was tested in an oxygen-saturated 0.1 mol / L potassium hydroxide (KOH) electrolyte using a rotating ring disk electrode (RRDE) device. The results are as follows: the half-wave potential was 0.80-0.85 V, and the Tafel slope was 90-91 mV dec. -1 The electron transfer number is 3.9 to 4.0 electrons, the H2O2 yield is less than 1%, and after 10,000 cyclic voltammetry scans (CV), the half-wave potential shifts to the left by only 10 to 12 mV.

[0016] For the OER process, the OER catalytic performance of the high entropy spinel oxide supported graphene catalyst was tested in an oxygen-saturated 1 mol / L potassium hydroxide (KOH) electrolyte using a rotating ring disk electrode (RRDE) device. The overpotential value was 350-360 mV, and the Tafel slope was 90-92 mV dec. -1 , after 10,000 cyclic voltammetry scans (CV), the overpotential value only shifted to the right by 10 to 13 mV.

[0017] The beneficial effect of the present invention is that the high-entropy spinel oxide-loaded graphene catalyst provided by the present invention can be used as a catalyst for ORR and / or OER catalytic reactions, and exhibits excellent ORR and / or OER catalytic performance in the electrolyte, indicating that it has faster reaction kinetics characteristics.

[0018] A method for preparing a high-entropy spinel oxide-supported graphene catalyst of the present invention comprises the following steps:

[0019] S1: Preparation of polymetallic salt solution

[0020] Selecting corresponding metal salt solutions according to the metal elements in the high-entropy spinel oxide-supported graphene catalyst, mixing and dissolving them in deionized water to obtain a multi-metal salt solution;

[0021] S2: Coprecipitation

[0022] Stir evenly, add alkaline solution dropwise to the polymetallic salt solution to form a dark brown precipitate, until the pH value reaches 10-11, stop adding dropwise, continue stirring until the mixture is evenly mixed, and obtain a polymetallic hydroxide precipitate mixture;

[0023] S3 hydrothermal treatment

[0024] The polymetallic hydroxide precipitate mixture is transferred to a high-pressure reactor, subjected to hydrothermal reaction and heat preservation, cooled, washed multiple times, and dried and ground to obtain a high-entropy spinel oxide precursor;

[0025] S4: High temperature calcination

[0026] The high entropy spinel oxide precursor was transferred to a muffle furnace for high-temperature calcination, cooled and ground to obtain high entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles;

[0027] S5: Mixed solution

[0028] High entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles and graphene oxide (GO) were mixed in an ethanol-water solution according to the mass ratio and ultrasonically mixed to obtain a uniformly mixed composite solution.

[0029] S6: Secondary hydrothermal

[0030] The uniformly mixed composite solution was transferred to a high-pressure reactor for secondary hydrothermal reaction and heat preservation, followed by cooling and drying to obtain a (FeCrCuNiMn)3O4 / rGO composite catalytic material, which is a high-entropy spinel oxide-supported graphene catalyst.

[0031] In S1, the corresponding metal salt solutions are respectively an iron-based salt solution, a chromium-based salt solution, a copper-based salt solution, a nickel-based salt solution, and a manganese-based salt solution. The iron-based salt solution is selected from at least one of a ferric chloride solution, a ferric nitrate solution, and a ferric sulfate solution, preferably a ferric nitrate solution; the chromium-based salt solution is selected from at least one of a chromium chloride solution and a chromium nitrate solution, preferably a chromium nitrate solution; the copper-based salt solution is selected from at least one of a copper chloride solution, a copper nitrate solution, and a copper sulfate solution, preferably a copper chloride solution; the nickel-based salt solution is selected from at least one of a nickel chloride solution and a nickel nitrate solution, preferably a nickel chloride solution; and the manganese-based salt solution is selected from at least one of a manganese chloride solution and a manganese nitrate solution, preferably a manganese chloride solution.

[0032] In the S1, the multi-metal salt solution has a molar ratio of Fe:Cu:Ni:Mn:Cr=1:1:1:1:0.5; the molar concentrations of the metal salt solutions are: Fe molar concentration of 1 mol / L, Cu molar concentration of 1 mol / L, Ni molar concentration of 1 mol / L, Mn molar concentration of 1 mol / L, and Cr molar concentration of 0.5 mol / L. The inductively coupled plasma spectroscopy (ICP-AES) test results show that the mass percentage (W%) of each metal element is

[0033] W Fe =14.1~14.2%、W Cu =16.1~16.2%、W Ni =16.5~16.7%、W Mn =14.2~14.3%、W Cr =9.1~9.2%.

[0034] In the above-mentioned S2, the alkaline solution is preferably a NaOH solution, and the molar concentration of NaOH in the NaOH solution is 1 mol / L.

[0035] In the S2, stir evenly for more than 2 hours, and continue stirring until the mixture is evenly mixed for more than 2 hours.

[0036] In the step S3, the hydrothermal reaction is held at a temperature of 180-200° C. for 10-15 hours.

[0037] In the step S3, the cooling method is furnace cooling.

[0038] In the step S3, the drying temperature is 80°C.

[0039] In the above-mentioned S4, the high-temperature calcination temperature is 700-1000° C., and the calcination holding time is 2-3 hours.

[0040] In the above-mentioned S4, the cooling method is air cooling.

[0041] In the S5, the mass ratio of (FeCrCuNiMn)3O4 nanoparticles to graphene oxide (GO) is 1: (1.1-1.5), preferably 1:1.2, and the volume ratio of the ethanol aqueous solution is deionized water to anhydrous ethanol = 2:1, and the ultrasonic mixing time is 2 hours.

[0042] In the S6, the secondary hydrothermal temperature is 160°C to 180°C, the holding time is 5 to 6 hours, the cooling method is furnace cooling, and the drying temperature is 80°C.

[0043] The beneficial effects of the present invention are as follows: the high-entropy spinel oxide-loaded graphene catalyst prepared by the present invention is a (FeCrCuNiMn)3O4 / rGO composite catalytic material coupled with a graphene material, the preparation process is controllable and pollution-free, the operation is simple, the cost is low, and the high-entropy spinel oxide-coupled graphene composite material can be prepared on a large scale.

[0044] Compared with the sintering preparation method, the hydrothermal method has the advantages of being environmentally friendly, simple to operate, mild reaction conditions and low energy consumption.

[0045] The present invention uses reduced graphene oxide, which has better water solubility and is easier to disperse than ordinary graphene.

[0046] The advantages of electrostatic adsorption coupling with high entropy spinel oxides can be realized.

[0047] In order to solve the third technical problem mentioned above, the technical solution adopted by the present invention is:

[0048] The application of the high entropy spinel oxide supported graphene catalyst provided by the present invention to drive flexible zinc-air batteries under normal and low temperature conditions is specifically as follows:

[0049] The flexible zinc-air battery used in the present invention comprises a catalytic layer, a current collector, a polyacrylic acid (PAA) gel electrolyte and a gas diffusion layer.

[0050] The catalytic layer of the present invention comprises a high-entropy spinel oxide-supported graphene catalyst and a Nafion binder. Preferably, the solid-liquid ratio of the high-entropy spinel oxide-supported graphene catalyst to the Nafion binder is (6-8 mg): (15-20 μL).

[0051] The current collector of the present invention is made of either nickel foam or carbon paper.

[0052] The gas diffusion layer of the present invention is made of a hydrophobic breathable membrane or a hydrophobic carbon cloth.

[0053] The high entropy spinel oxide supported graphene catalyst provided by the present invention can drive a zinc-air battery at 100 mA cm at room temperature. -2 Under the condition of high discharge power of 100-120mW cm -2 , within the 10h test time range, the flexible zinc-air battery can be bent at any angle. In low temperature environment, at 80mAcm -2 Under the condition of high discharge power of 60-70mW cm -2 During the 12-hour test, the voltage difference between the two flexible zinc-air batteries remained stable at 0.70 to 0.75 V. Outdoors in the cold winter, the LED light panel was successfully lit to ensure normal operation.

[0054] The beneficial effects of the present invention are as follows: the flexible zinc-air battery driven by the high-entropy spinel oxide-supported graphene catalyst provided by the present invention exhibits the performance of a flexible zinc-air battery driven by an excellent commercial catalyst Pt / C+RuO2, both at room temperature and low temperature environments, showing excellent low-temperature battery performance and low-temperature adaptability, excellent cycle performance and discharge power density, and low-temperature applicability and application reliability. It can effectively replace the commercial catalyst Pt / C+RuO2 for use in low-temperature zinc-air batteries, effectively solving the application problems of precious metal catalysts such as poor catalytic stability, poor low-temperature adaptability, high cost and pollution, and provides an effective and practical application prospect for the development of the low-temperature zinc-air battery field. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] In order to more clearly illustrate the specific technical solutions of the embodiments of the present invention, the following will introduce the drawings required in the embodiments of the present invention. The following drawings are some embodiments of the present invention.

[0056] Figure 1 The X-ray diffraction (XRD) patterns of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention are shown.

[0057] Figure 2 This is the XRD pattern of Example 1 of the present invention at different synthesis and calcination temperatures.

[0058] Figure 3 This is a field emission scanning electron microscope (SEM) image of Example 1 of the present invention.

[0059] Figure 4 This is the electron probe energy dispersive spectroscopy (EDS) diagram of Example 1 of the present invention.

[0060] Figure 5 This is a field emission transmission electron microscope (TEM) image of Example 1 of the present invention.

[0061] Figure 6 1 is a comparison diagram of the linear voltammetry (LSV) curves of the ORR stage of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 4 of the present invention.

[0062] Figure 7 This is a comparison chart of the Tafel slopes in the ORR stage of Example 1, Comparative Example 1, and Comparative Example 2 of the present invention;

[0063] Figure 8 Graph showing the electron transfer number and H2O2 yield of the high entropy spinel oxide supported graphene catalyst prepared in Example 1 of the present invention;

[0064] Figure 9This is the LSV curve of ORR of the high-entropy spinel oxide-supported graphene catalyst prepared in Example 1 of the present invention after 10,000 cyclic voltammetry curves.

[0065] Figure 10 This is a comparison diagram of the linear voltammetry (LSV) curves of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 4 in the OER stage of the present invention.

[0066] Figure 11 This is a comparison chart of the Tafel slopes in the OER stage of Example 1, Comparative Example 1, and Comparative Example 2 of the present invention.

[0067] Figure 12 LSV curve of OER of the high entropy spinel oxide supported graphene catalyst prepared in Example 1 of the present invention after 10,000 cyclic voltammetry curves.

[0068] Figure 13 Comparison of charge and discharge polarization curves of the flexible zinc-air battery at room temperature and low temperature for Example 1 of the present invention and Comparative Example 3; (a) is at room temperature (25°C); (b) is at low temperature (-25°C).

[0069] Figure 14 This is a comparison chart of the discharge power of the flexible zinc-air battery of Example 1 of the present invention and Comparative Example 3 at room temperature and low temperature; (a) is room temperature (25°C); (b) is low temperature (-25°C).

[0070] Figure 15 This is a constant current charge and discharge performance curve diagram of the low-temperature flexible zinc-air battery at different bending angles according to Example 1 of the present invention.

[0071] Figure 16 This is a comparison chart of the low-temperature constant-current charge-discharge cycle performance of Example 1 of the present invention and Comparative Example 3.

[0072] Figure 17 This is a diagram showing the change in open-circuit voltage of Example 1 of the present invention in a low-temperature environment for a long time. DETAILED DESCRIPTION

[0073] The present invention provides a method for preparing a high-entropy spinel oxide-supported graphene catalyst and its application in a low-temperature flexible zinc-air battery. To clarify the purpose, technical solution, and effects of the claimed invention, the present invention is described in further detail below. It should be understood that the specific embodiments described herein are intended only to illustrate the present invention and are not intended to limit the present invention.

[0074] The testing equipment used for the catalytic performance of the high-entropy spinel oxide-supported graphene catalyst provided by the present invention is Chenhua 760 testing equipment.

[0075] Example 1

[0076] A high-entropy spinel oxide-supported graphene catalyst, the preparation method of which is as follows:

[0077] Weigh 1mol / LFe(NO3)2·6H2O, 1mol / LNiCl2·6H2O, 1mol / L MnCl2·4H2O, 1 mol / L CuCl2·2H2O, and 0.5 mol / L Cr(NO3)3·9H2O were placed in 30 mL of deionized water and mixed and stirred until uniform. 40 mL of 1 mol / L NaOH solution was added dropwise with stirring until the pH value reached 11. The mixture was magnetically stirred for 2 h to obtain a multi-metal hydroxide precipitate mixture, which was then transferred to a high-temperature reactor, kept at 200°C for 12 h, cooled with the furnace, washed and dried, and transferred to a muffle furnace for high-temperature calcination at 1000°C for 2 h. The mixture was air-cooled and ground to obtain high-entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles. The mass ratio of high-entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles to graphene oxide (GO) was 1:1.2. The volume of the ethanol-water solution added was 60 mL, including 20 mL of anhydrous ethanol and 40 mL of deionized water. The ultrasonic mixing time was 2 h. The hydrothermal temperature was 180° C., the holding time was 6 h, the cooling method was furnace cooling, and the drying temperature was 80° C. A (FeCrCuNiMn)3O4 / rGO composite catalytic material was obtained.

[0078] Example 2

[0079] A high-entropy spinel oxide-supported graphene catalyst, the preparation method of which is as follows:

[0080] Weigh 1mol / LFe(NO3)2·6H2O, 1mol / LNiCl2·6H2O, 1mol / L MnCl2·4H2O, 1 mol / L CuCl2·2H2O, and 0.5 mol / L Cr(NO3)3·9H2O were placed in 30 mL of deionized water and mixed and stirred until uniform. 40 mL of 1 mol / L NaOH solution was added dropwise with stirring until the pH value reached 10. The mixture was magnetically stirred for 2 h to obtain a multi-metal hydroxide precipitate mixture, which was then transferred to a high-temperature reactor, kept at 180°C for 15 h, cooled with the furnace, washed and dried, and transferred to a muffle furnace for high-temperature calcination at 700°C for 2 h. The mixture was air-cooled and ground to obtain high-entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles. The high-entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles and graphene oxide (GO) were mixed in a mass ratio of 1:1.2. The volume of the ethanol-water solution added was 60 mL, including 20 mL of anhydrous ethanol and 40 mL of deionized water, and the ultrasonic mixing time was 2 h. The secondary hydrothermal temperature was 160° C., the holding time was 6 h, the cooling method was furnace cooling, and the drying temperature was 80° C. A (FeCrCuNiMn)3O4 / rGO composite catalytic material was obtained.

[0081] Example 3

[0082] A high-entropy spinel oxide-supported graphene catalyst, the preparation method of which is as follows:

[0083] Weigh 1mol / LFe(NO3)2·6H2O, 1mol / LNiCl2·6H2O, 1mol / L MnCl2·4H2O, 1 mol / L CuCl2·2H2O, and 0.5 mol / L Cr(NO3)3·9H2O were placed in 30 mL of deionized water and mixed and stirred until uniform. 40 mL of 1 mol / L NaOH solution was added dropwise with stirring until the pH value reached 11. The mixture was magnetically stirred for 2 h to obtain a multi-metal hydroxide precipitate mixture, which was then transferred to a high-temperature reactor, kept at 200°C for 12 h, cooled with the furnace, washed and dried, and transferred to a muffle furnace for high-temperature calcination at 800°C for 3 h. The mixture was air-cooled and ground to obtain high-entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles. The mass ratio of high-entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles to graphene oxide (GO) was 1:1.3. The volume of the ethanol-water solution added was 60 mL, including 20 mL of anhydrous ethanol and 40 mL of deionized water, and the ultrasonic mixing time was 2 h. The hydrothermal temperature was 170° C., the holding time was 6 h, the cooling method was furnace cooling, and the drying temperature was 80° C. A (FeCrCuNiMn)3O4 / rGO composite catalytic material was obtained.

[0084] Example 4

[0085] A high-entropy spinel oxide-supported graphene catalyst, the preparation method of which is as follows:

[0086] Weigh 1mol / LFe(NO3)2·6H2O, 1mol / LNiCl2·6H2O, 1mol / L MnCl2·4H2O, 1 mol / L CuCl2·2H2O, and 0.5 mol / L Cr(NO3)3·9H2O were placed in 30 mL of deionized water and mixed and stirred until uniform. 40 mL of 1 mol / L NaOH solution was added dropwise with stirring until the pH value reached 11. The mixture was magnetically stirred for 2 h to obtain a multi-metal hydroxide precipitate mixture, which was then transferred to a high-temperature reactor, kept at 200°C for 12 h, cooled with the furnace, washed and dried, and transferred to a muffle furnace for high-temperature calcination at 1000°C for 2 h. The mixture was air-cooled and ground to obtain high-entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles. The high-entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles and graphene oxide (GO) were mixed in a mass ratio of 1:1.5. The volume of the ethanol-water solution added was 60 mL, including 20 mL of anhydrous ethanol and 40 mL of deionized water, and the ultrasonic mixing time was 2 h. The hydrothermal temperature was 180° C., the holding time was 5 h, the cooling method was furnace cooling, and the drying temperature was 80° C. A (FeCrCuNiMn)3O4 / rGO composite catalytic material was obtained.

[0087] Example 5

[0088] A high-entropy spinel oxide-supported graphene catalyst, the preparation method of which is as follows:

[0089] Weigh 1mol / LFe(NO3)2·6H2O, 1mol / LNiCl2·6H2O, 1mol / L MnCl2·4H2O, 1 mol / L CuCl2·2H2O, and 0.5 mol / L Cr(NO3)3·9H2O were placed in 30 mL of deionized water and mixed and stirred until uniform. 40 mL of 1 mol / L NaOH solution was added dropwise with stirring until the pH value reached 11. The mixture was magnetically stirred for 2 h to obtain a multi-metal hydroxide precipitate mixture, which was then transferred to a high-temperature reactor, kept at 190°C for 10 h, cooled with the furnace, washed and dried, and transferred to a muffle furnace for high-temperature calcination at 900°C for 2 h. The mixture was air-cooled and ground to obtain high-entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles. The high-entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles and graphene oxide (GO) were mixed in a mass ratio of 1:1.4. The volume of the ethanol-water solution added was 60 mL, including 20 mL of anhydrous ethanol and 40 mL of deionized water, and the ultrasonic mixing time was 2 h. The hydrothermal temperature was 180° C., the holding time was 6 h, the cooling method was furnace cooling, and the drying temperature was 80° C. A (FeCrCuNiMn)3O4 / rGO composite catalytic material was obtained.

[0090] Comparative Example 1

[0091] The (FeCuNiMn)3O4 / rGO composite catalytic material was prepared by the following method:

[0092] The preparation method is the same as that of Example 1, except that the Cr element is not contained. 1 mol / LFe(NO3)2·6H2O, 1 mol / LNiCl2·6H2O, 1 mol / L MnCl2·4H2O, and 1 mol / LCuCl2·2H2O need to be weighed respectively to obtain the (FeCuNiMn)3O4 / rGO composite catalytic material.

[0093] Comparative Example 2

[0094] The (FeNiMn)3O4 / rGO composite catalytic material was prepared by the following method:

[0095] The preparation method is consistent with that of Example 1, except that Cr and Cu elements are not contained. 1 mol / LFe(NO3)2·6H2O, 1 mol / LNiCl2·6H2O, and 1 mol / LMnCl2·4H2O need to be weighed respectively to obtain the (FeNiMn)3O4 / rGO composite catalytic material.

[0096] Comparative Example 3

[0097] Pt / C+RuO2 catalyst was used as comparative example 3.

[0098] Comparative Example 4

[0099] Preparation of (FeCrCuNiMn)3O4 / C composite catalytic material, the preparation method is as follows:

[0100] The preparation method is consistent with that of Example 1, except that graphene is added.

[0101] The (FeCuNiMn)3O4 / rGO composite catalytic materials prepared in Comparative Example 4 and Example 1 are compared in terms of catalytic performance. The ORR half-wave potential of (FeCrCuNiMn)3O4 / C is (0.79V), which is much lower than (FeCuNiMn)3O4 / rGO (0.83V), and the OER overpotential value of (FeCrCuNiMn)3O4 / C is (380mV), which is much higher than (FeCuNiMn)3O4 / rGO (359mV).

[0102] Comparative Example 5

[0103] The (FeCrCuNiMn)3O4 / rGO composite catalytic material was prepared by the following method:

[0104] 1 mol / L Fe(NO₃)₂·6H₂O, 1 mol / L NiCl₂·6H₂O, 1 mol / L MnCl₂·4H₂O, 1 mol / L CuCl₂·2H₂O, and 0.5 mol / L Cr(NO₃)₃·9H₂O were weighed and placed in 30 mL of deionized water, stirred until homogeneous, and then spray pyrolyzed to obtain a high-entropy oxide (HEO) with the molecular formula (FeCrCuNiMn)₃O₄. The HEO and graphene oxide (GO) were then ultrasonically mixed for 2 hours in 60 mL of deionized water at a mass ratio of 1:1.2. The hydrothermal temperature was 180°C, the heat was maintained for 6 hours, and the mixture was cooled by furnace cooling. The drying temperature was 80°C. This resulted in the (FeCrCuNiMn)₃O₄ / rGO composite catalytic material.

[0105] The method of the comparative example is a sintering preparation method, while the hydrothermal method adopted in the present invention has the advantages of being environmentally friendly, simple to operate, mild reaction conditions and low energy consumption.

[0106] Test Example 1

[0107] The structural characterization of the above high entropy spinel oxide supported graphene catalyst is as follows;

[0108] Figure 1The X-ray diffraction (XRD) patterns of Example 1, Comparative Example 1, and Comparative Example 2 of the present invention are shown. The XRD diffraction peaks of Example 1, Comparative Example 1, and Comparative Example 2 are consistent with all diffraction peaks of the Fe3O4 standard card (PDF#01-072-6170), showing characteristics of a spinel cubic structure, corresponding to the (220), (311), (400), (511), and (440) crystal planes, respectively.

[0109] The diffraction peaks at around 26.1° in Example 1, Comparative Example 1 and Comparative Example 2 correspond to the (002) crystal plane of rGO.

[0110] Figure 2 The XRD patterns of Example 1 at different calcination temperatures show the changes in the synthesis process at different temperatures. When the synthesis temperature exceeds 600°C, the spinel structure gradually appears, while the (FeCuNiMn)3O4 phase structure is synthesized at 1000°C.

[0111] Figure 3 This is a field emission scanning electron microscope (SEM) image of Example 1 of the present invention. It can be concluded that the high entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles in Example 1 are uniformly distributed on the rGO surface.

[0112] Figure 4 This is an electron probe energy dispersive spectroscopy (EDS) diagram of Example 1 of the present invention, which confirms that the elements Fe, Cr, Cu, Ni, and Mn are uniformly distributed.

[0113] Figure 5 This is a field emission transmission electron microscopy (TEM) image of Example 1 of the present invention. Example 1 shows that its lattice fringes are 0.24 nm and 0.21 nm, corresponding to the (311) and (400) crystal planes, respectively.

[0114] Test the ORR / OER catalytic performance of (FeCrCuNiMn)3O4 / rGO composite catalytic material;

[0115] Prepare electrocatalyst ink as follows:

[0116] The catalyst ink consists of a suspension of catalyst powder (3 mg), isopropanol (482 μL, 99.8%), and Nafion solution (18 μL, 5 wt%), which was ultrasonicated for 2 hours. The loading mass on the glassy carbon electrode (GC) was approximately 0.3 mg cm -2 .

[0117] The electrochemical test catalytic performance system is as follows:

[0118] Electrochemical measurements were performed on a Chenhua 760 electrochemical workstation using a standard three-electrode system. A glassy carbon electrode (GC), a platinum sheet, and a saturated calomel electrode (Hg / HgO) were used as the working electrode, counter electrode, and reference electrode, respectively.

[0119] Figure 6 The half-wave potential performance of the ORR process of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 4 of the present invention is compared. The ORR stage half-wave potential performance is tested in a 0.1 mol / L KOH solution. It can be seen that the half-wave potential value of Example 1 is the highest (0.83 V). It is higher than the half-wave potential values ​​of Comparative Example 1 (0.75 V), Comparative Example 2 (0.73 V) and Comparative Example 4 (0.79 V), indicating that Example 1 has higher ORR catalytic activity.

[0120] Figure 7 The Tafel slope of Example 1 (91.2 mV dec -1 ) is lower than that of comparative example 1 (126.2mV dec -1 ), Comparative Example 2 (149.1mV dec -1 ). This shows that Example 1 has faster ORR reaction kinetics than the comparative example.

[0121] Figure 8 RRDE measurements of the catalytic process in Example 1 revealed a four-electron transfer mechanism, with a H₂O₂ yield of less than 1% within the 0.2V to 1.0V range. This indicates that the four-electron transfer mechanism in Example 1 achieves a more efficient and rapid electrocatalytic reaction, while suppressing the formation of H₂O₂, reducing side reactions and corrosion, and improving the electrochemical activity and energy conversion efficiency of the battery.

[0122] Figure 9 In the LSV curve of ORR of Example 1 after 10,000 cyclic voltammetry curves, the half-wave potential only decreases by 11 mV, indicating that Example 1 has excellent electrochemical cycling stability in the ORR stage.

[0123] Figure 10 The overpotential performance comparison of the OER process of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 4 of the present invention is shown. The overpotential value of the OER stage was tested in a 1 mol / L KOH solution. The overpotential value of Example 1 (359 mV) was the lowest. It was lower than the overpotential values ​​of Comparative Example 1 (396 mV), Comparative Example 2 (409 mV), and Comparative Example 4 (390 mV), indicating that Example 1 has higher OER catalytic activity.

[0124] Figure 11 The Tafel slope of Example 1 (90.6 mV dec -1 ) is lower than that of comparative example 1 (104.69mV dec -1), Comparative Example 2 (122.5mV dec -1 ). This shows that Example 1 has faster OER reaction kinetics than the comparative example.

[0125] Figure 12 In the LSV curve of OER of Example 1 after 10,000 cyclic voltammetry curves, the overpotential value only increased by 13 mV, indicating that Example 1 has excellent electrochemical cycling stability in the OER stage.

[0126] Performance test of flexible zinc-air battery at room temperature and low temperature;

[0127] Flexible zinc-air batteries undergo battery performance testing on the BluePower battery testing system CT3004A.

[0128] For comparative experiments, the performance of Example 1 and Comparative Example 3 was compared under normal temperature and low temperature environments.

[0129] In the flexible zinc-air battery performance test, 15 mg of the catalyst prepared in Example 1 was dispersed in 0.6 mL of isopropanol, and a Nafion solution (20 μL, 5 wt%) was added. The mixture was ultrasonically dispersed for 3 h to obtain a catalyst ink. 0.3 mL of the catalyst ink was evenly drop-coated onto the current collector surface in multiple batches and dried overnight in a drying oven at 60°C. The reaction area was 1×1 cm. A PAA hydrogel electrolyte, a waterproof and breathable layer, and a catalyst layer were combined to form a flexible zinc-air battery. The PAA hydrogel electrolyte consisted of 6 M KOH and 0.2 M Zn(Ac)2·2H2O. For Comparative Example 3, 15 mg of 40% Pt / C and RuO2 were weighed and the catalyst ink was prepared according to the above method.

[0130] Figure 13 This is a comparison diagram of the charge and discharge polarization curves of the flexible zinc-air battery at room temperature and low temperature of Example 1 of the present invention and Comparative Example 3; wherein, Figure 13 (a) is at 25℃. Figure 13 (b) is the low temperature condition of -25°C. It can be seen that the charge-discharge gap voltage values ​​of Example 1 under both normal temperature and low temperature conditions are smaller than those of Comparative Example 3.

[0131] Figure 14 This is a comparison chart of the discharge power of the flexible zinc-air battery at room temperature and low temperature of Example 1 and Comparative Example 3 of the present invention; wherein, Figure 14 (a) is at 25℃. Figure 14(b) is at a low temperature of -25°C. Under both normal and low temperature conditions, the peak discharge power of Example 1 is higher than that of Comparative Example 3. This indicates that Example 1 has a stronger instantaneous power output capability during discharge in a low-temperature environment, can efficiently convert chemical energy into electrical energy, and improves overall battery performance, outperforming Comparative Example 3. This demonstrates that the catalytic activity of Example 1 can effectively resist the problem of slow kinetics in low-temperature environments.

[0132] Figure 15 Figure 1 shows the constant current charge-discharge performance curves of the low-temperature flexible zinc-air battery of Example 1 of the present invention at different bending angles. After undergoing various bending deformations, the charge and discharge potential of the flexible zinc-air battery based on Example 1 remained nearly unchanged, demonstrating that Example 1 possesses excellent mechanical flexibility and stability in low-temperature environments.

[0133] Figure 16 This figure compares the low-temperature constant-current charge-discharge cycle performance of Example 1 and Comparative Example 3. After 12 hours of cyclic charge-discharge at -25°C, Example 1 still maintains a large charge-discharge voltage difference and cycle stability, with an average charge-discharge voltage difference of 0.73V, which is better than Comparative Example 3 (0.75V). This shows that Example 1 has excellent low-temperature cycle stability.

[0134] Figure 17 This is a graph showing the open-circuit voltage change of Example 1 of the present invention under long-term static conditions in a low-temperature environment. After the flexible zinc-air battery was static for 48 hours at -25°C, the open-circuit voltage decreased slowly, only by 30mV. This indicates that the low-temperature flexible zinc-air battery driven by Example 1 has good low-temperature adaptability and resistance to low-temperature degradation. This excellent performance demonstrates that the battery can operate stably in low-temperature environments, maintain good battery performance, and adapt to the needs of long-term static applications in cold conditions.

[0135] In summary, the present invention provides a method for preparing a high-entropy spinel oxide-supported graphene catalyst and its application in low-temperature flexible zinc-air batteries. The electrocatalyst prepared by the present invention, as a cathode catalyst for low-temperature flexible zinc-air batteries, exhibits excellent ORR / OER catalytic performance, high discharge power density, low-temperature cycling stability, and low-temperature adaptability. It outperforms the currently commercially available Pt / C+RuO2 catalyst in driving flexible zinc-air batteries at low temperatures, addressing the practical issue of slow electrocatalyst kinetics in low-temperature environments and providing a practical and effective scientific approach for the development of low-temperature zinc-air batteries.

[0136] The above description is only a partial embodiment of the present invention, and the present invention is not limited to the above detailed method. Any improvement of the present invention made by a person skilled in the art within the technical scope disclosed in the present invention by means of equivalent substitution or addition of auxiliary components shall be included in the scope of protection of the present invention.

Claims

1. A high entropy spinel oxide supported graphene catalyst, characterized in that The high-entropy spinel oxide supported graphene catalyst is composed of high-entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles uniformly dispersed on the surface of reduced graphene oxide sheets.

2. The high entropy spinel oxide supported graphene catalyst according to claim 1, characterized in that The molecular formula of the high-entropy spinel oxide supported graphene catalyst is (FeCrCuNiMn)3O4 / rGO, the mass percentage of Fe, Cr, Cu, Ni, and Mn is between 5% and 20%, and the mass percentage difference of each element does not exceed 8%; and / or, the mass ratio of high-entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles to reduced graphene oxide is 1:(1.1-1.5).

3. The high entropy spinel oxide supported graphene catalyst according to claim 2, characterized in that The mass percentages of the metal elements in the (FeCrCuNiMn)3O4 / rGO are respectively Fe: 14.1-14.2%, Cr: 9.1-9.2%, Cu: 16.1-16.2%, Ni: 16.5-16.7%, and Mn: 14.2-14.3%; and / or, the mass ratio of high-entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles to reduced graphene oxide is 1:1.

2.

4. The use of the high entropy spinel oxide supported graphene catalyst according to any one of claims 1 to 3, characterized in that: Application in ORR and / or OER electrocatalytic reaction processes and application driving low-temperature flexible zinc-air batteries.

5. The use of the high entropy spinel oxide supported graphene catalyst according to claim 4, characterized in that, Electrochemical tests show that in alkaline KOH solution, the ORR half-wave potential can reach 0.80V~0.85V, and the OER overpotential can reach 350mV~360mV.

6. An air cathode of a low-temperature flexible zinc-air battery, characterized in that: The flexible zinc-air battery comprises a catalytic layer formed by the high-entropy spinel oxide-loaded graphene catalyst according to any one of claims 1 to 3, and further comprises a current collector polyacrylic acid gel electrolyte and a gas diffusion layer.

7. A flexible zinc-air battery, characterized in that: An air cathode comprising the low-temperature flexible zinc-air battery according to claim 6.

8. The flexible zinc-air battery according to claim 7, characterized in that: The flexible zinc-air battery is -2 The discharge power is 100-120 mW cm -2 In the 10h test time range, the flexible zinc-air battery can be bent at any angle; in low temperature environment, at 80mAcm -2 The discharge power is 60-70 mW cm -2 Within the 12h test time range, the voltage difference of the flexible zinc-air battery is stable at 0.70-0.75V; in the cold winter outdoors, the LED light board is successfully lit to enable normal operation.

9. The method for preparing the high entropy spinel oxide supported graphene catalyst according to any one of claims 1 to 3, comprising the following steps: S1: Select corresponding metal salt solutions according to the metal elements in the high-entropy spinel oxide-supported graphene catalyst, mix and dissolve them in deionized water to obtain a multi-metal salt solution; S2: Stirring evenly, adding alkaline solution dropwise to the polymetallic salt solution to form a dark brown precipitate until the pH value reaches 10-11, stopping the dropwise addition, and continuing stirring until the mixture is evenly mixed to obtain a polymetallic hydroxide precipitate mixture; S3: transferring the polymetallic hydroxide precipitate mixture to a high-pressure reactor, carrying out a hydrothermal reaction and keeping the temperature, cooling, washing the product multiple times, and drying and grinding to obtain a high-entropy spinel oxide precursor; S4: transferring the high entropy spinel oxide precursor to a muffle furnace for high temperature calcination, cooling and grinding to obtain high entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles; S5: mixing high entropy spinel oxide (FeCrCuNiMn)3O4 nanoparticles and graphene oxide in an ethanol aqueous solution according to a mass ratio, and ultrasonically mixing them to obtain a uniformly mixed composite solution; S6: The uniformly mixed composite solution is transferred to a high-pressure reactor for secondary hydrothermal reaction and heat preservation, followed by cooling and drying to obtain a (FeCrCuNiMn)3O4 / rGO composite catalytic material, which is a high-entropy spinel oxide-supported graphene catalyst.

10. The method for preparing a high entropy spinel oxide-supported graphene catalyst according to claim 9, wherein: In the S3, the hydrothermal reaction insulation temperature is 180-200°C, and the insulation time is 10-15 hours; in the S4, the high-temperature calcination temperature is 700-1000°C, and the calcination insulation time is 2-3 hours; in the S6, the secondary hydrothermal temperature is 160-180°C, and the insulation time is 5-6 hours.

Citation Information

Cited By

  • High-entropy oxide composite negative electrode material and preparation method and application thereof

    CN121506923A